Analysis of Damage to Network Time Protocol (NTP) Server on Cengkareng Radar Equipment in Perum LPPNPI Branch JATSC - Abrar, Raihan; Fatonah, Feti; Kusuma, Adenia (Fidelity : Jurnal Teknik Elektro, 2024)
The On The Job Training (OJT) program which will be implemented in 2022-2023 also includes collaboration with the LPPNPI Jakarta Air Traffic Service Center (JATSC) Branch Office. On The Job Training (OJT) involves various divisions that handle various equipment and facilities that support aviation safety, including equipment such as the Network Time Protocol (NTP) Server used to synchronize the time of equipment connected to the server network at the Jakarta Air Traffic Services Center (JATSC), thereby ensuring accurate operating times for all connected equipment. All of these efforts aim to improve safety and efficiency in aviation at the national and international levels. However, in this case, in operation, not all equipment always runs well, as does Network Time Protocol (NTP) server 1 at the LPPNPI Jakarta Air Traffic Services Center (JATSC) Branch. The purpose of this research is that the author wants to solve the problems that occur in On The Job Training (OJT) activities at Perum LPPNPI Jakarta Air Traffic Services Center (JATSC) Branch.